Kinetic study of a Bacterial Consortium isolated from soil contaminated with crude oil - Husain, Iman A. F.; Al-Khatib, Ma'an Fahmi Rashid; Alam, Md. Zahangir; Muyibi, Suleyman Aremu (AJBAS Journal, 2011)
Laboratory study was carried out to isolate hydrocarbon utilizing bacteria from crude-oil contaminated soil (COCS) to test their potential for the bioremediation of COCS. Twenty strains were isolated by enrichment culture using minimal salt medium with crude oil as sole carbon source. The twenty isolated strains were purified and monitored for their growth by monitoring the optical density (OD600). The twelve best growing strains were selected to form four bacterial consortiums. Each consortium contains three strains combined with accordance to their growth. The four consortiums were tested for their growth and the best one (Cons.1) was selected for the kinetics study and the biodegradability test. From the first order kinetic study, the maximum growth rate μmax of the selected consortium was 0.02 hr-1 while the half saturation constant ks was 2.2%v/v total petroleum hydrocarbons (TPH). The selected strains showed a potential for biodegradation of crude oil in soil slurry with removal up to 95% within seven days which would further be used for the bioremediation of COCS.